The Effect of Financial Literacy on Village Government Business Performance - Anis, Anis; Zulkifli, Makhmud; Pranjoto, Gatot Heru (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study was conducted to study the impact of financial literacy and financial management on the performance of Village government businesses (Village-Owned Enterprises) located in Lobuk Village, Bluto District, Sumenep Regency. As a village economic institution, Village government plays a strategic role in improving the progress and prosperity of the community. The level of financial literacy and effective financial management are considered to be able to influence the operational success of Village government, especially in making strategic decisions, optimizing the use of funds, and increasing profits. This study adopted a descriptive quantitative method involving all administrators, employees, and tenants of Pelangi Nusantara Village government kiosks in Lobuk Village as the population and sample. There are three variables studied, two of which are independent variables, namely Financial Literacy (X1) and Financial Management (X2), while the dependent variable is Village government Business Performance (Y). Data analysts use several techniques including data quality testing, multiple regression analysis and determination coefficient testing. Hypothesis testing was conducted through t-test (partial) and F-test (simultaneous) with the help of IBM SPSS software version 25. The research findings revealed that financial literacy does not affect Village Government Business Performance, financial management has a significant positive effect on Village Government Business Performance, financial literacy and financial management have a significant effect simultaneously on Village Government business performance.